Aspiration of Aluminum Beverage Can Tab: Case Report and Literature Review. (28th May 2017) - Elghouche, Alhasan N.; Lobo, Brian C.; Ting, Jonathan Y.
Abstract : We describe the case of a 16-year-old male who aspirated a beverage can tab resulting in significant functional impairment. Since the introduction of beverage can opening tabs ("pop-tops" or "pull-tabs") nearly 50 years ago, five cases of their aspiration have been reported in the literature and this is the first case to report tracheal lodgment. We describe the clinical course for this patient including the inadequacy of radiographic evaluation and a significant delay in diagnosis. We highlight unique features of small aluminum foreign bodies that require consideration and mention a potential change in epidemiology associated with evolving product design. Our primary objective is increased awareness among otolaryngologists that radiography is unreliable for diagnosis or localization of small aluminum foreign bodies. The patient history must therefore be incorporated with other imaging modalities and/or endoscopic evaluation. Also, given the marked prevalence of aluminum beverage cans, we suspect that the inadvertent aspiration of can tabs is more common than indicated by the paucity of published reports.